Heat Transfer of Single and Binary Systems in Pool Boiling - Abid, Balasim A.; Sultan, Abbas J. (Al-Khwarizmi Engineering Journal, 2010)
The present research focuses on the study of the effect of mass transfer resistance on the rate of heat transfer in pool boiling. The nucleate pool boiling heat transfer coefficients for binary mixtures (ethanol-n-butanol, acetone-n-butanol, acetone-ethanol, hexane-benzene, hexane-heptane, and methanol-water) were measured at different concentrations of the more volatile components. The systems chosen covered a wide range of mixture behaviors.The experimental set up for the present investigation includes electric heating element submerged in the test liquid mounted vertically. Thermocouple and a digital indictor measured the temperature of the heater surface. The actual heat transfer rate being obtained by multiplying the voltmeter and ammeter readings. A water cooled coil condenses the vapor produced by the heat input and the liquid formed returns to the cylinder for re-evaporation.The boiling results show that the nucleate pool boiling heat transfer coefficients of binary mixtures were always lower than the pure components nucleate pool boiling heat transfer coefficients. This confirmed that the mass transfer resistance to the movement of the more volatile component was responsible for decrease in heat transfer and that the maximum deterioration that was observed at a point was the absolute concentration differences between vapor and liquid phases at their maximum. All the data points were tested with the most widely known correlations namely those of Calus-Leonidopoulos, Fujita and Thome. It was found that Thome's correlation is the more representative form, for it gave the least mean and standard deviations.